Urban trust in Kenya and Tanzania: Cooperation in the provision of public goods - Burbidge, D (Taylor and Francis (Routledge), 2014)
Literature connecting ethnic diversity with public goods provision has found public goods to be poorly and unevenly supplied in ethnically heterogeneous communities. Scrutinising this hypothesis, the study contrasts an ethnically homogenous community in Kenya with an ethnically heterogeneous one in Tanzania, documenting levels of trust and cooperation in public goods provision. Interviews and focus groups with market-sellers of Mwanza (Tanzania) and Kisumu (Kenya) reveal how the two professionally similar populations differ starkly in the way they participate in public goods, and in an opposite direction to that which would be predicted by the current literature on ethnicity. On the topic of the organisation of security and cleaning within markets in Mwanza, ethnically heterogeneous market-sellers' sense of solidarity facilitates a greater degree of seller-on-seller trust. In Kisumu, in contrast, with participants reflective of the dominant Luo ethnicity, the lack of state provision of public services has seen a feeble and individualistic response. The findings demonstrate how ethnic distribution matters less for public goods provision than commitments amongst citizens themselves and between citizens and local authorities.